Behavioral problems of the hearing-impaired students in the Sultanate of Oman: teachers perspective study = المشكلات السلوكية للطلبة المعاقين سمعيا من وجهة نظر معلميهم في سلطنة عمان - Mubark Hamed AL-Saighi, Hanaa; Ahmed Mohamed, Ismaiel Hassanein (International Organization Center of Academic Research (OCERINT), 2020)
This quantitative study discusses the level of behavioral problems of the hearing impaired from the viewpoint of their teachers in the Sultanate of Oman, and the problem lies in the loss of this category of hearing sense or its presence in a simple manner, which leads to difficulty in communication and interaction with those around the hearing impaired; this affects their behavior and makes it socially unacceptable , Which requires finding proposals or solutions that help the hearing impaired in harmony and integration with their normal teachers and peers. The study aimed to diagnose the behavioral problems of hearing impaired students (deaf, hard of hearing, cochlear implant) from the viewpoint of their teachers, as well as to analyze the factors that lead to reducing the behavioral problems of the hearing impaired. The study relied on the descriptive analytical approach. The study population consisted of all the teachers and hearing impaired teachers, who numbered (266) teachers. The study sample included all members of the study community. The researcher used a questionnaire comprising (32) expressions of behavioral problems for the disabled: the problem of aggression (9 phrases), the problem of excessive activity (6) phrases, the problem of abuse (7) phrases, the problem of lying (6) phrases, and the problem of social withdrawal (4) phrases. The results showed that the level of behavioral problems of students ranged between medium and low, first came the problem of excessive activity, then the problem of aggression, followed by the problem of social withdrawal, the problem of lying, and finally the problem of abuse. The researcher recommended: integrating the hearing impaired completely into the school community in terms of (morning assembly, and participation in school activities). ****************************************************************************** تناقش هذه الدراسة الكمية مستوى المشكلات السلوكية للمعاقين سمعيا من وجهة نظر معلميهم في سلطنة عمان، وتكمن المشكلة في فقدان هذه الفئة لحاسة السمع أو وجودها بشكل بسيط الأمر الذي يؤدي إلى صعوبة في الاتصال والتفاعل مع المحيطين بالمعاق سمعيا؛ فيؤثر ذلك على سلوكهم ويجعله غير مقبول اجتماعيا، مما يستوجب إيجاد مقترحات أو حلول تساعد المعاقين سمعيا على الانسجام والاندماج مع معلميهم وأقرانهم الأسوياء. هدفت الدراسة إلى تشخيص المشكلات السلوكية للطلبة المعاقين سمعيا (الصم، ضعاف السمع، زراعي القوقعة) من وجهة نظر معلميهم، كما هدفت إلى تحليل العوامل التي تؤدي للحد من المشكلات السلوكية للمعاقين سمعيا. اعتمدت الدراسة على المنهج الوصفي التحليلي، تكون مجتمع الدراسة من جميع معلمات ومعلمين المعاقين سمعيا، البالغ عددهم (266) معلما ومعلمة، وشملتْ عينة الدراسة كافة أفراد مجتمع الدراسة. استخدمت الباحثة استبيان يضم (32) عبارة عن المشكلات السلوكية للمعاقين: مشكلة العدوانية (9) عبارات، مشكلة النشاط الزائد (6) عبارات، ومشكلة الاعتداء (7) عبارات، ومشكلة الكذب (6) عبارات، ومشكلة الانسحاب الاجتماعي (4) عبارات. بينت النتائج: تراوح مستوى المشكلات السلوكية للطلبة بين المتوسط والمنخفض، جاءت أولا مشكلة النشاط الزائد، ثم مشكلة العدوانية، تلتها مشكلة الانسحاب الاجتماعي، فمشكلة الكذب، وأخيرا مشكلة الاعتداء. أوصت الباحثة: دمج المعاقين سمعيا دمجا كليا في المجتمع المدرسي من حيث (طابور الصباح، والمشاركة في الأنشطة المدرسية).